2017
DOI: 10.14503/thij-16-6059
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable Scaffolds in Spontaneous Coronary Artery Dissection: Long-Term Follow-Up in 4 Patients

Abstract: Spontaneous coronary artery dissection is a rare condition, and diagnosis and treatment are challenging among patients who present with acute coronary syndrome. Typically, the condition affects young females who have no underlying atherosclerotic disease. To date, few cases of bioresorbable scaffold implantation for the treatment of spontaneous coronary artery dissection have been reported. Therefore, we describe the cases of 4 patients whom we treated with scaffolds. We evaluated the long-term results by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
1
0
1
Order By: Relevance
“…Feasibility of SCAD treatment with poly‐ l ‐lactic acid (PLLA) Absorb BRS has been reported in several case reports and in a subanalysis of the RAI registry; specifically, the latter study reported no cardiovascular events at a mean follow‐up of 18 months in 18 SCAD patients treated with PLLA‐BRS. Moreover, both OCT and CT angiography confirmed the acceptable results of Absorb implantation in SCAD patients at 1 and 3 years of follow‐up, respectively. However, due to significantly higher rates of scaffold thrombosis with Absorb implantation compared to metallic Everolimus‐eluting stents in patients with coronary artery disease, Absorb was recently withdrawn from the market.…”
Section: Discussionsupporting
confidence: 54%
“…Feasibility of SCAD treatment with poly‐ l ‐lactic acid (PLLA) Absorb BRS has been reported in several case reports and in a subanalysis of the RAI registry; specifically, the latter study reported no cardiovascular events at a mean follow‐up of 18 months in 18 SCAD patients treated with PLLA‐BRS. Moreover, both OCT and CT angiography confirmed the acceptable results of Absorb implantation in SCAD patients at 1 and 3 years of follow‐up, respectively. However, due to significantly higher rates of scaffold thrombosis with Absorb implantation compared to metallic Everolimus‐eluting stents in patients with coronary artery disease, Absorb was recently withdrawn from the market.…”
Section: Discussionsupporting
confidence: 54%
“…Various case reports have illustrated technical success with various alternative interventional techniques and approaches; however, in the absence of large prospective clinical trials, no specific interventional strategy has been demonstrated as a superior alternative to PCI with conventional stenting. Further research into bioresorbable scaffolds (76), balloon angioplasty alone, use of cutting balloons (77), extended stent lengths, and intravascular imaging guidance for stent placement is required to optimise interventional approaches to patients presenting with SCAD requiring intervention.…”
Section: Alternative Interventional Approachesmentioning
confidence: 99%
“…Некоторые эксперты предлагают использовать биорезорбируемые скаффолды вместо стентов с лекарственным покрытием (СЛП) для уменьшения частоты данных осложнений [43][44][45][46][47]. Наряду с этим некоторые авторы также продемонстрировали эффективность и безопасность применения режущих баллонов (РБ) при СДКА [48][49][50]…”
Section: прогнозunclassified